PENANGANAN PERILAKU OPEN BO (BOOKING ONLINE) DI UNIT PELAKSANA TEKNIS PERLINDUNGAN PEREMPUAN DAN ANAK (UPT PPA) KOTA MAKASSAR (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2021)
The main problem in this study is how to handle the behavior of Open BO (Booking Online) in the Technical Implementation Unit for Women and Children Protection (UPT PPA) Makassar City? Protection of Women and Children (UPT PPA) Makassar City in dealing with Open BO (Booking Online) behavior; 2) To find out the obstacles of the Technical Implementation Unit for the Protection of Women and Children (UPT PPA) of Makassar City in dealing with Open BO (Booking Online) behavior. This research is a qualitative research with a sociological approach method located in the Technical Implementation Unit for the Protection of Women and Children (UPT PPA) Makassar City. The data sources in this study are based on primary data sources and secondary data sources. The method of data collection is by observation, interviews, and documentation. The instruments in this study were interview guides, cameras, voice recorders, and stationery. After all the data was collected, the researcher conducted data analysis with data reduction, data presentation, comparative analysis techniques, and drawing conclusions. The results of this study indicate that, the form of handling the Technical Implementation Unit for the Protection of Women and Children (UPT PPA) of Makassar City in dealing with Open BO (Booking Online) behavior, namely: a) conducting an assessment (assessment); b) provide assistance to victims; c) perform the best service in accordance with the office soup and subsequently fostered in a safe house (shelter); and d) carry out religious training in a safe house (shelter). Obstacles to the Technical Implementation Unit for the Protection of Women and Children (UPT PPA) of Makassar City in dealing with Open BO (Booking Online) behavior, namely: a) current regulations such as the Law on the Eradication of the Crime of Trafficking in Persons (PTPPO) are not effectively used; b) it is difficult to find open BO networks (pimps); c) there is no cooperation and is not recognized by his family; and d) there is no ongoing control or subsequent supervision. Keywords : Handling Behavior of Open BO and UPT PPA.